2016
DOI: 10.1126/science.aab4138
|View full text |Cite
|
Sign up to set email alerts
|

AMP-activated protein kinase mediates mitochondrial fission in response to energy stress

Abstract: Mitochondria undergo fragmentation in response to electron transport chain (ETC) poisons and mitochondrial DNA–linked disease mutations, yet how these stimuli mechanistically connect to the mitochondrial fission and fusion machinery is poorly understood. We found that the energy-sensing adenosine monophosphate (AMP)–activated protein kinase (AMPK) is genetically required for cells to undergo rapid mitochondrial fragmentation after treatment with ETC inhibitors. Moreover, direct pharmacological activation of AM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

45
856
3
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 899 publications
(909 citation statements)
references
References 41 publications
45
856
3
5
Order By: Relevance
“…Whether or not these effects can be neutralized by substrate supplementation or stimulation of fusion genes such as mitofusin (Mfn), or if pathological changes in mitochondrial dynamics may more generally be rescued by increased substrate delivery, are questions that should be considered for future studies. In this respect, it has recently been reported that cellular energy deficiency induces mitochondrial fission via AMPK-dependent Fis1 and Drp1 recruitment (33). This fission has been interpreted as being prerequisite for the removal of faulty mitochondria by mitophagy (33), but our findings offer the alternative possibility that mitochondrial fragmentation enhances glycolytic metabolite delivery to mitochondria and thus maintains ATP output during times of high energetic demand.…”
Section: Discussioncontrasting
confidence: 36%
“…Whether or not these effects can be neutralized by substrate supplementation or stimulation of fusion genes such as mitofusin (Mfn), or if pathological changes in mitochondrial dynamics may more generally be rescued by increased substrate delivery, are questions that should be considered for future studies. In this respect, it has recently been reported that cellular energy deficiency induces mitochondrial fission via AMPK-dependent Fis1 and Drp1 recruitment (33). This fission has been interpreted as being prerequisite for the removal of faulty mitochondria by mitophagy (33), but our findings offer the alternative possibility that mitochondrial fragmentation enhances glycolytic metabolite delivery to mitochondria and thus maintains ATP output during times of high energetic demand.…”
Section: Discussioncontrasting
confidence: 36%
“…We found that the administration of the uncouplers alone did not show a direct impact on the growth or gene expression of tumor cells. Mitochondrial energy metabolism is closely linked with cellular metabolism via mTOR and AMPK (36,49,50). We found that uncouplers combined with PD-1 blockade activate not only the AMPK but also the mTOR pathway.…”
Section: Discussionmentioning
confidence: 89%
“…PTMs of the mitochondrial adaptor protein Mff also promote recruitment of Drp1 to the OMM. In mouse embryonic fibroblasts, cellular stress induced by inhibitors of the mitochondrial electron transport chain triggers AMP-kinasemediated phosphorylation of Mff at S155 and S172, culminating in recruitment of Drp1 and mitochondrial fission (Toyama et al, 2016).…”
Section: Post-translational Regulation Of Mitochondrial Fission and Fmentioning
confidence: 99%